2017
DOI: 10.1111/tbed.12634
|View full text |Cite
|
Sign up to set email alerts
|

ORF3adeletion in field strains of porcine-transmissible gastroenteritis virus in China: A hint of association with porcine respiratory coronavirus

Abstract: Porcine-transmissible gastroenteritis virus (TGEV) is a pathogenic coronavirus responsible for high diarrhoea-associated morbidity and mortality in suckling piglets. We analysed the TGEV ORF3 gene using nested polymerase chain reaction and identified an ORF3a deletion in three field strains of TGEV collected from piglets in China in 2015. Eight TGEV ORF3 sequences were obtained in this study. Phylogenetic tree analysis of ORF3 showed that the eight TGEV ORF3 genes all belonged to the Miller cluster. CH-LNCT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Other coronaviruses may also use ANPEP as an entry mediator. Due to genome similarity porcine respiratory coronavirus (a TGEV mutant) (Zhang et al 2017 ) likely uses ANPEP, and other less related viruses such as porcine deltacoronavirus, another swine enteropathogen, may use ANPEP to gain entry into the cell (Li et al 2018 ). Clearly additional whole animal studies need to be conducted to better understand the molecules that these viruses use to gain entry.…”
Section: Discussionmentioning
confidence: 99%
“…Other coronaviruses may also use ANPEP as an entry mediator. Due to genome similarity porcine respiratory coronavirus (a TGEV mutant) (Zhang et al 2017 ) likely uses ANPEP, and other less related viruses such as porcine deltacoronavirus, another swine enteropathogen, may use ANPEP to gain entry into the cell (Li et al 2018 ). Clearly additional whole animal studies need to be conducted to better understand the molecules that these viruses use to gain entry.…”
Section: Discussionmentioning
confidence: 99%
“…Many types of viruses cause diarrhoea in animals, including TGEV (Zhang, Zhu, Zhu, Chen et al., ), swine enteric coronaviruses (SeCoVs) (Belsham et al., ), PEDV (Lohse et al., ; Tian et al., ; Zhang, Tian et al., ), porcine deltacoronavirus (Lee et al., ; Mai et al., ; Saeng‐Chuto et al., ) and rotaviruses (Kim et al., ). Rotaviruses cause acute dehydrating diarrhoea in various hosts, including children and young animals (Jiang, Liu, & Tan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the disease always happened in swine-producing areas of the world (1,3), and reported many times in China in recent years (4)(5)(6)(7)(8). Epidemiological investigations have shown that TGEV is often present in the spring and autumn in the northeast of China, sometimes in mixed infections with other diarrhea virus, and caused viral enteritis and severe diarrhea in all ages of pigs, especially with high mortality in suckling piglets (9,10).…”
Section: Introductionmentioning
confidence: 99%